Regulation of WRKY46 Transcription Factor Function by Mitogen-Activated Protein Kinases in Arabidopsis thaliana - Sheikh, Arsheed H.; Eschen-Lippold, Lennart; Pecher, Pascal; Hoehenwarter, Wolfgang; Sinha, Alok K.; Scheel, Dierk; Lee, Justin (Frontiers in Plant Science, 2016)
Abstract Mitogen-activated protein kinase (MAPK) cascades are central signalling pathways activated in plants after sensing internal developmental and external stress cues. Knowledge about the downstream substrate proteins of MAPKs is still limited in plants. We screened Arabidopsis WRKY transcription factors as potential targets downstream of MAPKs, and concentrated on characterizing WRKY46 as a substrate of the MAPK, MPK3. Mass spectrometry revealed in vitro phosphorylation of WRKY46 at amino acid position S168 by MPK3. However, mutagenesis studies showed that a second phosphosite, S250, can also be phosphorylated. Elicitation with pathogen-associated molecular patterns (PAMPs), such as the bacterial flagellin-derived flg22 peptide led to in vivo destabilization of WRKY46 in Arabidopsis protoplasts. Mutation of either phosphorylation site reduced the PAMP-induced degradation of WRKY46. Furthermore, the protein for the double phosphosite mutant is expressed at higher levels compared to wild-type proteins or single phosphosite mutants. In line with its nuclear localization and predicted function as a transcriptional activator, overexpression of WRKY46 in protoplasts raised basal plant defence as reflected by the increase in promoter activity of the PAMP-responsive gene, NHL10, in a MAPK-dependent manner. Thus, MAPK-mediated regulation of WRKY46 is a mechanism to control plant defence.